Size of National Assemblies: The Classic Derivation of the Cube-Root Law is Conceptually Flawed - Margaritondo, Giorgio (Frontiers in Physics, 2021)
For half a century, the analysis of the size of national assemblies was dominated by the famous cube-root relation with the population. However, a revisitation of that historical work with a physicist’s approach reveals basic conceptual problems that fatally undermine its conclusions. Furthermore, the assembly size evaluation exceeds the accuracy of all power equations, which cannot be reliably used for political analysis.